Association between epicardial adipose tissue and Duke treadmill score: Epicardial Adipose Tissue and Duke Treadmill Score - Cerit, Levent; Cerit, Zeynep (Progress in Nutrition, 2019)
Duke treadmill score (DTS) is a well-known prognostic tool in patients with suspected coronary artery disease (CAD). DTS is a stronger predictor than ST-segment response alone in a treadmill test.  Epicardial adipose tissue (EAT) has anatomical and functional contiguity with myocardium and coronary arteries. Increased EAT thickness (EATT) is strongly associated with CAD. This study aimed to evaluate the association between EAT and DTS. The data of patients were retrospectively analysed for the demographic features, echocardiographic parameters including ejection fraction, EATT, biochemical parameters, and DTS. The study population consisted of 698 patients admitted to the outpatient clinic with chest pain. DTS was calculated as originally described: DTS = exercise time – (5 × ST deviation) – (4 × exercise angina). Patients were divided into two groups according to the DTS values: low risk (DTS≥ +5), intermediate to high risk (IHR) (DTS< +4). According to the EATT, the patients were divided into two groups: increased EATT (≥5.1), normal EATT (